(untitled) (Research, Society and Development, 2021)
In Piauí, American Visceral Leishmaniasis (AVL) has great relevance because the state is one of the endemic centers of the disease. Thus, the objective of this study was to describe the epidemiological profile of Visceral Leishmaniasis (VL) in the state of Piauí, from 2012 to 2018. This is a descriptive, quantitative, population-based study, using secondary data referring to the epidemiological aspects of cases of Visceral Leishmaniasis (VL) notified in the state of Piauí for the years 2012 to 2018, registered in the Notifiable Diseases Information System (SINAN). During the study period, 1550 cases of Visceral Leishmaniasis were reported in the state of Piauí. The mean incidence rate of the disease in the period was 6.37 cases per 100,000 inhabitants. There was a predominance of records of Visceral Leishmaniasis in a population residing in urban areas (68.45%). The peri-urban and rural areas had a smaller share of notifications and together accounted for 28.51% of the total records. It was also identified that 78.7% of cases were confirmed in the metropolitan region of Teresina. The LVA lethality was on average 5.9%, which ranged from 3.66% (2012) to 7.72% (2014). Thus, based on the results, it is possible to point out the endemic behavior of the disease and the importance of the rear of the health apparatus in the city of Teresina (capital) in directing the diagnosis and epidemiological investigation. Regarding this last point, the importance of expanding the improvement of health equipment and services to the interior of the state of Piauí is reiterated, in order to advocate better coverage of cases and, therefore, determine early notification and treatment.